Case Report: Giant left atrial cystic tumor: myxoma or intracardiac blood cyst? - Xiao, Weizhang; Qin, Jing; Feng, Jia; Jiang, Feng; Chen, Xinming; Cao, Xiang; Xue, Qun; Shi, Jiahai (Frontiers in Cardiovascular Medicine, 2024)
Background: Primary cardiac tumors are uncommon, with the majority being benign myxomas. Cystic myxoma, a particularly rare type of benign cardiac tumor, demands cautious differential diagnosis from other cardiac tumors. Case Summary: A 43-year-old male patient presenting with intermittent dyspnea was referred to our department for surgical evaluation. Transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) unveiled an intra-left atrial cyst, which was subsequently found to be blood-filled during a video-assisted microinvasive heart surgery. Pathological examination depicted a cyst wall filled with small stellate and fat spindle cells, along with a mucoid matrix, indicating a diagnosis of cystic myxoma. Conclusions: We herein presented a rare case of an adult patient with cystic myxoma, initially misdiagnosed as an intracardiac blood cyst (CBC) prior to surgery, and ultimately verified via pathological findings.